Study on Drug Utilisation in Medicine Department Under National Health Scheme of Ayushman Bharath Arogya Karnataka in Tertiary Care Teaching Hospital - P L, Basavanna; B M, Dayana; V A, Dileep; Sam, Hebseba; M D, Pavitha; P Choudary, Ravindra (Indian Journal of Pharmacy Practice)
Background Information: India being the developing country the progress of diseases is a challenge to healthcare system with a dense population and the available healthcare services may be expensive to a group of society and hence all citizens may not be a beneficiary of an advanced health care system. To overcome the loopholes of the entire available scheme in a state it was merged into an ABARK scheme. Materials and Methods: It’s a prospective observational study of 550 patients, to assess and analyse Drug Utilization in Medicine Department under National Health Insurance Scheme of Ayushman Bharat Arogya Karnataka (ABARK). Results: Out of 550 patients 52% of our study population had more than one comorbid condition, highest being the cardiovascular disease. Drugs were mostly prescribed in monotherapy (78.06%) and only 21.14% were prescribed in combination of drugs. Among the 5980 drugs prescribed, the highest category were Multivitamins (18.32%) followed by Antimicrobials (18.1%) and the least prescribed were CNS Agent (2.55%). Drugs prescribed by generic name were 35.39% and brand name was 64.61%. Average number of drugs per prescription is 10.87. About 61.47% of drug prescribed from WHO EML list and 74.01% was prescribed from NLEM list. Highest dosage form prescribed were injectables (46.1%) followed by tablets (35.1%) and least prescribed was Mouth gargle (0.03%). The ABARK awareness survey shows moderate awareness among the study population. Conclusion: Rational prescribing is seen due to majority of drug prescribed in accordance with WHO EML and NLEM list. Certain degree of polypharmacy was seen, as the average drug per prescription was high.
Keywords: BARK; General Medicine; Prescription; DUE; WHO EML; NLEM